Angels flight - Connelly, Michael (New York : Warner Books, 1999)
At the foot of Angels Flight, an inclined railway in the heart of downtown Los Angeles, a black lawyer is murdered, bringing cheers from policemen whom he frequently sued for brutality. The case is given to detective Harry Bosch and right away he discovers tampering of evidence.
National College of Business and Arts
Keywords: Police -- Fiction; Detective and mystery fiction